Guidelines from the Seerah of Prophet Muhammad (P.B.U.H) in Establishing the Unity of Ummah in this age - Shah, Syed Muhammad Tahir (Journal of Islamic and Religious Studies, 2022)
Islam is a universal religion and an advocate of world-wide peace and unity among people of different backgrounds. It preaches its followers about the unity of the whole humanity. In several verses of Qur’ān and in the sayings of Prophet Muhammad (PBUH), the Muslims Ummah is directed to be united and harmonious. Prophet Muhammad (PBUH) also presented a great role model from his own life and practices (Sīrah) to establish and maintain unity among the Muslim Ummah. He (PBUH) established brotherhood among the Muhājrīn and the Anṣār and suggested it as a model practice to the whole Ummah. He (PBUH) also narrated the benefits of unity and the disadvantages of dispersal in his sayings. He suggested the effective solutions of differences of opinions and other clashes among the Muslims. This research focuses on deriving the solutions of maintaining the unity and brotherhood in resolving the clashes and differences of ideology among Muslims in the light of the teachings of Islam, especially from The Sīrah (life practice) of The Prophet Muhammad (P.B.U.H) in this age.